Ectoparasites of small mammals in four localities of wildlife reserves in Peninsular Malaysia - Madinah, A.; Fatimah, Abang; Mariana, A..; M.T, Abdullah (Southeast Asian J Trop Med Public Health, 2011)
Field surveys of ectoparasites on rodents and scandents were conducted in four localities of wildlife reserves in Peninsular Malaysia from October 2008 to November 2009. A total of 16 animals comprising 5 species of hosts were caught and examined for ectoparasites. The hosts examined were Maxomys rajah,Maxomys whiteheadi, Leopoldamys sabanus, Lariscus insignis and Tupaia glis. Of these hosts, 9 genera, consisting of 14 species of ectoparasites were extracted. Three species of ticks (Ixodidae), 7 species of mesostigmatid mites (Laelaptidae), 3 species of chiggers (Trombiculidae) and 1 species of listrophorid mites (Listrophoriidae) were identified. The infestation rate of ectoparasites observed ranged from 12.5% to 62.5%. Among the ectoparasites found, Ixodes granulatus and Leptotrombidium deliense are of known medical importance.